The future of work: How G20 countries can leverage digital-industrial innovations into stronger high-quality jobs growth - Marco Annunziata; Hendrik Bourgeois (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The wave of digital-industrial innovation which begins to disrupt vast sectors of the global economy has fueled fear of a potential adverse impact on jobs and wages. This paper argues that digitalindustrial innovations make human capital more important than ever and the focus needs to shift to the complementarity between new technologies and human abilities. In particular, more effort should be devoted to (i) understanding what new skills will be needed, and how existing jobs will change; (ii) upgrading education and professional training schemes; (iii) reforming labor market institutions to support a future where a larger share of workers will change jobs and employers more frequently; (iv) reforming social benefits systems and bolstering social safety nets to smooth the economic transition and cushion the impact on the worst-affected workers. This paper presents an analysis of the challenges, addresses the key areas of action, and puts forward specific proposals, including policy actions, industry initiatives, and further research projects. The authors argue that the G20 could and should champion a comprehensive approach to leverage digital-industrial innovations for faster job creation and growth, with initiatives to re-align demand and supply of skills, labor market reforms, redesigned social safety nets, measures to promote digital innovation and facilitate the adoption of skills-augmenting technologies, and strengthened private sector training programs.
Keywords: J20; J23; J24; J62; J68; O32; O33; M5; I28; E24; D24; 330; innovation; productivity; technological unemployment; training; education; manufacturing; R&D; investment